Qual a percepção do empresário sobre o Goodwill na venda do seu negócio? - Oliveira, Cristiane Sobral de (2015)
This study aimed to know the Goodwill and the matters to which involves using the methodology, based on a multiple comparative case study, which checks the perception of the entrepreneur on Goodwill in the sale of your business. The study was conducted among the concepts which covers several authors and a questionnaire with questions and objective responses (made through a table structured in the study concepts), involving two companies selected for convenience of the researcher. Then it is performed the analysis of the data obtained and the necessary considerations. The research approach is qualitative, exploratory and descriptive. Through the concepts proposed by the authors related to the theme, called active factor and what it represents in a company, which are the assets and rights capable of generating cash flow in the short, medium and long term, divided into Tangible and intangible assets, and so Goodwill is considered the most contentious issue in accounting, because conceptually it is difficult to understand and its measurement is a much-discussed factor, but there is no accounting standards both domestic and international, any doubts about the need for their registration (in purchasing a business), called the Goodwill Purchased Purchased or when the purchase occurs is for sale, then there is its measurement because the fact is a negotiation. In trading who buys acquires who sells scraps of business. Regarding the perception of entrepreneurs which the survey was conducted, knowledge is basic for the understanding of that subject "Goodwill" comes from the company itself